Exiting a Lawless State - Hoff, Karla; Stiglitz, Joseph E. (World Bank, Washington, DC, 2012)
An earlier paper showed that an economy could be trapped in an equilibrium state in which the absence of the rule of law led to asset-stripping, and the prevalence of asset-stripping led to the absence of a demand for the rule of law, highlighting a coordination failure. This paper looks more carefully at the dynamics of transition from a non-rule-of-law state. The paper identifies a commitment problem as the critical feature inhibiting the transition: the inability, under a rule of law, to forgive theft. This can lead to the perpetuation of the non-rule-of-law state, even when it might seem that the alternative is Pareto-improving.